Critical Illness Insurances: Challenges and Opportunities for Insurers - Gatzert, Nadine; Mägebier, Alexander (Risk Management and Insurance Review, 2015)
Since the first introduction of critical illness insurance in 1983 in South Africa, the product has successfully spread to some insurance markets, especially in Asian and Anglophone countries, but market penetration remains low in other countries. For this reason and because of the increasing relevance of dread diseases, the aim of this article is to provide a first comprehensive overview of challenges and opportunities associated with critical illness products for insurers. Toward this end, we first present the various product designs, as well as the developments that have taken place within the market before comparing this form of coverage to alternative insurance products in order to better assess the market potential. Based on these assessments, we thoroughly discuss the major challenges and opportunities within the market from the insurer's perspectiv
Keywords: Critical illness insurance; dread disease market; health insurance; product design

Securitization of Disability Risk via Bonds and Swaps - Mägebier, Alexander (The Journal of Risk Finance, 2015)
Purpose The purpose of this paper is to show that healthier lifestyles, medical progress and the change of working conditions have been identified as potential sources for systematic disability risk. Design/methodology/approach Thus, the aim of this paper is to provide a first discussion regarding the advantages and detriments in comparison with mortality-linked bonds and swaps as well as regarding potential disability-linked indices and the potential use. Findings The discussion is followed by an introduction of a potential design and a corresponding valuation of disability bonds and swaps. Originality/value However, no disability-linked securities have been defined and discussed so fa

The Impact of Disability Insurance on a Portfolio of Life Insurances - Mägebier, Alexander; Gatzert, Nadine (North American Actuarial Journal, 2016)
The aim of this paper is to study the impact of disability insurance on an insurer’s risk situation for a portfolio also consisting of annuity and term life contracts. We provide a model framework using discrete time non-homogeneous bivariate Markov renewal processes and in a simulation study focus on diversification benefits as well as potential natural hedging effects (risk-minimizing or risk-immunizing portfolio compositions) that may arise within the portfolio due to the different types of biometric risks. Our analyses emphasize that disability insurances are a less efficient tool to hedge shocks to mortality and that their high sensitivity towards shocks to disability risks cannot be easily counterbalanced by other life insurance products. However, the addition of disability insurance can still considerably lower the overall company ris

Valuation and Risk Assessment of Disability Insurance using a Discrete Time Trivariate Markov Renewal Reward Process - Mägebier, Alexander (Insurance Mathematics & Economics, 2013)
In disability insurance, the impact of the duration since the inception of disability on future recovery and mortality rates has been modeled by bivariate Markov renewal processes and the associated semi-Markov process, but these processes do not incorporate potential dependences between the durations in two successive states. Thus, the aim of this paper is to introduce a discrete time trivariate Markov renewal reward model, an associated formula for higher moments and a corresponding simulation that include the potential dependence between the durations, i.e. the inter-arrival times, in two successive states. The proposed model is compared with two alternative models that do not include this dependenc